2018
DOI: 10.1186/s12936-018-2316-3
|View full text |Cite
|
Sign up to set email alerts
|

Presence of novel triple mutations in the pvdhfr from Plasmodium vivax in Mangaluru city area in the southwestern coastal region of India

Abstract: BackgroundGenes encoding dihydrofolate reductase (dhfr) and dihydropteroate synthase (dhps) are the targets of sulfadoxine–pyrimethamine (SP) present in artemisinin based combination therapy (ACT; artesunate + sulfadoxine pyrimethamine) for Plasmodium falciparum. Although SP is generally not used to treat vivax infection, mutations in dhfr and dhps that confer antifolate resistance in Plasmodium vivax are common; which may be attributed to its sympatric existence with P. falciparum. Current study was aimed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 18 publications
2
4
0
Order By: Relevance
“…These findings agree with previously published reports showing low prevalence (less than 5%) of triple and quadruple mutant pvdhfr and pvdhps haplotypes in P. vivax parasite populations from Iran, Pakistan and India (Table 2) [21,22,[26][27][28][29][30][31][36][37][38][39]. In the wider study region, it was observed that the pyrimethamine resistance marker at position 117 in pvdhfr arose first and was followed by the subsequent mutation in positions 117 and 58, conferring increasing levels of resistance as report earlier [23,[26][27][28][29][30][31].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings agree with previously published reports showing low prevalence (less than 5%) of triple and quadruple mutant pvdhfr and pvdhps haplotypes in P. vivax parasite populations from Iran, Pakistan and India (Table 2) [21,22,[26][27][28][29][30][31][36][37][38][39]. In the wider study region, it was observed that the pyrimethamine resistance marker at position 117 in pvdhfr arose first and was followed by the subsequent mutation in positions 117 and 58, conferring increasing levels of resistance as report earlier [23,[26][27][28][29][30][31].…”
Section: Discussionsupporting
confidence: 93%
“…The frequencies of SP resistance related pvdhfr and pvdhps mutations have been extensively reported from various malaria-endemic areas, including Thailand [8,[11][12][13][14], Cambodia [15], Myanmar [16], Vietnam [17], Indonesia [18], Papua New Guinea [19], Madagascar [20] and India [21][22][23][24]. However, reports from Afghanistan and Middle East countries are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, double and single mutants were found at overall proportion of 11.9% and 17%, respectively. Double mutants R 58 N 117 were predominant in this study, especially in Delhi, as also previously reported from southern and western parts of India (i.e., Tamil Nadu, Karnataka, and West Bengal) [ 77 79 ]. This finding is also consistent with other P. vivax endemic countries such as China–Myanmar border, Ethiopia, and Sudan [ 75 , 80 , 81 ].…”
Section: Discussionsupporting
confidence: 87%
“…Quadruple 57L/58R/61M/117T, triple 57L/58R/117 and double pvdhfr (57L/117N) mutant haplotypes have been associated with in vitro drug resistance 16 . This study found pvdhfr double mutant S58R + S117N in 25% of clinical isolates reported from neighboring countries like India, Afghanistan and Iran [27][28][29] .…”
Section: Discussionmentioning
confidence: 52%